Origins and Development of Initiation of Free Radical Polymerization Processes - Dietrich Braun (International Journal of Polymer Science)
At present worldwide about 45% of the manufactured plastic materials and 40% of synthetic rubber are obtained by free radical polymerization processes. The first free radically synthesized polymers were produced between 1910 and 1930 by initiation with peroxy compounds. In the 1940s the polymerization by redox processes was found independently and simultaneously at IG Farben in Germany and ICI in Great Britain. In the 1950s the systematic investigation of azo compounds as free radical initiators followed. Compounds with labile C–C-bonds were investigated as initiators only in the period from the end of the 1960s until the early 1980s. At about the same time, iniferters with cleavable S–S-bonds were studied in detail. Both these initiator classes can be designated as predecessors for “living” or controlled free radical polymerizations with nitroxyl-mediated polymerizations, reversible addition fragmentation chain transfer processes (RAFT), and atom transfer radical polymerizations (ATRP).